HEART RATE COMPUTATION IMPLEMENTED ON FIELD PROGRAMMABLE GATE ARRAY BOARD - Ivanna K. Timotius (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2010)
Heart rate is the most basic information of heart activities. This paper aims to describe a possible real time system to detect electrocardiogram (ECG) signal, count the R-R interval of the ECG signal, and compute the heart rate. This project is implemented successfully using field programmable gate array (FPGA) board.